A database study on incidence and trends in traumatic lower-extremity amputations in the United States. Issue 4 (16th July 2022) - Herzog, Leah N.; Johnson, Charles A.; Gross, Christopher E.
Abstract : Background: There is minimal focus on traumatic lower-extremity amputations due to their relatively low incidence, but they often come with a higher morbidity and mortality than their upper extremity counterparts. The purpose of this study was to evaluate the incidence and trends of lower extremity amputations in the United States over 10 yr. Methods: The National Electronic Injury Surveillance System (NEISS) was queried from 2008 to 2017 for lower-extremity amputations presenting to United States emergency departments. Date of presentation, age at presentation, amputated appendage, disposition, and cause of the amputation were reported and used for statistical analysis. Results: From 2008 to 2017, 393 patients were reported to have sustained lower-extremity amputations within the NEISS database with an estimated total of 11, 475 patients sustaining a lower-extremity amputation over the past 10 yr and an incidence of 2.2 per 100, 000 person-years. The incidence of lower-extremity amputations is highest in those under 5 years old. Lawnmowers were the most common mechanism of injury in all age groups. Discussion: Due to the high morbidity and mortality associated with these injuries, it is prudent to follow the trends in lower-extremity amputations. This is particularly important in promoting awareness and prevention of the more common mechanisms such as lawnmower incidents. Level of Evidence: Level IV.